Chronic Fluoxetine Treatment Suppresses Plasticity (Long-Term Potentiation) in the Mature Rodent Primary Auditory Cortex In Vivo. (25th February 2014) - Dringenberg, Hans C.; Branfield Day, Leora R.; Choi, Deanna H.
Abstract : Several recent studies have provided evidence that chronic treatment with the selective serotonin reuptake inhibitor (SSRI) fluoxetine can facilitate synaptic plasticity (e.g., ocular dominance shifts) in the adult central nervous system. Here, we assessed whether fluoxetine enhances long-term potentiation (LTP) in the thalamocortical auditory system of mature rats, a developmentally regulated form of plasticity that shows a characteristic decline during postnatal life. Adult rats were chronically treated with fluoxetine (administered in the drinking water, 0.2 mg/mL, four weeks of treatment). Electrophysiological assessments were conducted using an anesthetized (urethane) in vivo preparation, with LTP of field potentials in the primary auditory cortex (A1) induced by theta-burst stimulation of the medial geniculate nucleus. We find that, compared to water-treated control animals, fluoxetine-treated rats did not express higher levels of LTP and, in fact, exhibited reduced levels of potentiation at presumed intracortical A1 synapses. Bioactivity of fluoxetine was confirmed by a reduction of weight gain and fluid intake during the four-week treatment period. We conclude that chronic fluoxetine treatment fails to enhance LTP in the mature rodent thalamocortical auditory system, results that bring into question the notion that SSRIs act as general facilitators of synaptic plasticity in the mammalian forebrain.